EFICIENTIZAREA SISTEMULUI DE ACHIZIŢII PUBLICE DIN REPUBLICA MOLDOVA ÎN CONTEXTUL PREVEDERILOR LEGISLATIVE ALE UE - Rusu, Elena (CEP USM, 2016)
Autorul abordează întregul sistem de achiziţii publice ca un instrument necesar şi important de eficientizare a acestora în contextul prevederilor legislative ale UE. În baza analizei procesului de achiziţii publice în contextul prevederilor legislative ale UE autorul a constatat prezenţa unor nereguli şi disfuncţionalităţi la organizarea şi desfăşurarea procedurilor de achiziţii publice la nivel naţional. Ca urmare, sunt propuse unele direcţii eficiente care ar contribui la crearea unui sistem eficace de achiziţii publicepe baza principiilor de reglementare a acestora aplicate în UE.

Author deals with the whole system of public procurement as a necessary and important tool to streamline them in the context of the EU legislation. Based on the analysis of the procurement process in the context of the EU legislation, the author found the presence of irregularities and failures in organization and conduct of procurement procedures at national level, the conclusion was proposed some ways effective co ntribute to creating an effective procurement system based on the principles of solving them applied in the EU.
EFFICIE NT PUBLIC PROCUREMENT SYSTEM IN THE REPUBLIC OF MOLDOVA IN THE CONTEXT OF THE EU LEGISLATION
Keywords: sistemul achiziţiilor publice; achiziţii publice; reforme economice; public procurement system; economic reform public procurement system efficiency